Wood Modification: Characterization, Modelling and Applications - Sandak, Anna; Sandak, Jakub (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This Special Issue of Coatings presents the newest research outcome in the field of the enhancement of native wood properties through a wide range of chemical, biological, and physical agents. The broad spectrum of topics provides a comprehensive update regarding ongoing research in this field. Such a compilation can be an inspiration for the further development of multifunctional and sustainable coatings, revolutionizing the wood sector of the future.